1994
DOI: 10.1002/bbpc.19940980605
|View full text |Cite
|
Sign up to set email alerts
|

Deuteron NMR relaxation, phase diagrams, and isotope effects in liquid mixtures of tetrahydrofuran/d2O/salt

Abstract: NMR spin‐lattice relaxation time T1 and phase diagrams of deuterosubstituted tetrahydrofurans (THF‐hg, THF‐h4d4, THF‐d8) in D2O and D2O/salt (Salt = MeCl, Me = Na, K, Rb, Cs; CaCl2, AlCl3; MeOH, Me = Na, K) mixtures have been studied close to their lower critical solution points. It has been found that deuteration of THF leads to a shrinkage of the closed‐loop phase diagram THF‐h8‐xdx/D2O. It is an opposite and much stronger effect to the well‐known replacement of H2O by D2O in the system THF‐h8/H2O (D2O). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…48 It is reasonable to suppose that anions Cl Ϫ and SO 4 2Ϫ cause strengthening of the H bonds in water, whereas anions I Ϫ weakens them. As was obtained by NMR investigations, 23 the activation energy of the reorientational motion of the tetrahydrofuran molecule in water increases due to the addition of the salt KCl. It is evident that the H bonds between water and tetrahydrofuran molecules strengthen due to the presence of the Cl Ϫ anions.…”
Section: Electrolytic Impurities and Pressurementioning
confidence: 82%
“…48 It is reasonable to suppose that anions Cl Ϫ and SO 4 2Ϫ cause strengthening of the H bonds in water, whereas anions I Ϫ weakens them. As was obtained by NMR investigations, 23 the activation energy of the reorientational motion of the tetrahydrofuran molecule in water increases due to the addition of the salt KCl. It is evident that the H bonds between water and tetrahydrofuran molecules strengthen due to the presence of the Cl Ϫ anions.…”
Section: Electrolytic Impurities and Pressurementioning
confidence: 82%
“…Maximum melting points for THF hydrate have been reported in the range of (277. 15-278.15) K [4][5][6][7][8]. Because of the ease with which THF hydrate forms, and the fact that at room temperature water and THF are completely miscible, the rather complex phase behavior taking place in this system is not apparent.…”
Section: Introductionmentioning
confidence: 99%
“…Matouš et al [4] identified a broad, closed loop with lower and upper consolute temperatures of approximately 344 K (53.5 wt%) and 410 K (48 wt%), respectively. Their study, and a more recent one by Balevicius et al [5], were undertaken to characterize the critical behavior in the system and clarify and describe substantial isotope effects on liquid miscibility. Rosso and Carbonnel [6] and Carbonnel and Rosso [7] determined the phase diagram at low temperatures and found a miscibility gap with a critical temperature of approximately 286 K and a peritectic reaction at 278 K forming the structure II clathrate hydrate at a composition of 17 : 1 H 2 O : THF.…”
Section: Introductionmentioning
confidence: 99%
“…6,9 Recently, the presence of multiple critical ͑hypercritical͒ points has also been identified in this system. We have previously investigated THF/ H 2 O / NaCl solution using various techniques such as Fourier transform infrared ͑FTIR͒, NMR, and critical opalescence, 5,6,9 and we have found that it exhibited unique temperature versus composition region of a weak turbidity, a long equilibration time, and fascinating isotopic effects.…”
Section: Resultsmentioning
confidence: 89%
“…6,[17][18][19][20] In particular, the difference of chemical shifts of nuclei involved in equilibrium association processes along the phase boundary may be taken as an order parameter. 6,[17][18][19][20] In particular, the difference of chemical shifts of nuclei involved in equilibrium association processes along the phase boundary may be taken as an order parameter.…”
Section: Introductionmentioning
confidence: 99%